Centered Leadership - Barsh, Joanna; Lavoie, Johanne (Recorded Books, 2014)
What enables some talented people to rise to the top and live their full ambitions at work and in life, while others stop short? In 2008, Joanna Barsh launched and sponsored Tthe Centered Leadership Project at McKinsey and & Company to answer that very question. In the process, they uncovered what distinguishes leaders who are successful from those who achieve true greatness. They called it Centered Leadership because these leaders find their balance in the midst of chaos and lead from their most resourceful self to unleash the potential of others. In the business bestseller, How Remarkable Women Lead , Barsh described Centered Leadership' s five capabilities and the research that underpins it. Here, with colleague Johanne Lavoie, she 30-year McKinsey veteran Joanna Barsh provides a practical, actionable field guide for implementation. Since 2008, Barsh, Lavoie and others at McKinsey have travelled the globe giving seminars, leading programs, workshops, and keynotes helping men and women to build these capabilities . In Centered Leadership , Barsh and Lavoie will guide you through the Centered Leadership program. You' ll find the interactive tools, exercises, and practices that have helped the men and women in Centered Leadership programs gain the skills, courage and confidence to unleash their potential and that of those around them. And, along the way, you' ll read inspiring stories of men and women leaders who demonstrate the power of these skills in action. Those early in their careers will learn how to use these skills to explore their passions and accelerate their professional development. Those forming families will be able to use them to reconcile manage work and life to get the most out of both. And those who have already achieved success will be able use these practices to reach their next leadership horizon. No matter what stage you are currently at in your career, or what level of leadership you aspire to, this book will equip you with the tools to unlock your own Centered Leader and achieve more positive impact at work and outside it.